Aspekty efektivnosti při volbě profese a školy: Přizpůsobují se pražské střední školy potřebám podniků? - Vladimír Benáček (Charles University in Prague, Institute of Economic Studies (IES), 2010)
– In this paper we study three crucial questions of economic decision-making: a) How are the people motivated in the choice of profession (career) and schools? This is also a decision that deals with the criteria for building the human capital of various specialisations. b) Can enterprises rely on the supply of new workers that should be qualified by skills for filling the future specialised demands of enterprises? c) Do the admissions into secondary schools, as intermediaries between the previous two, adjust to labour inputs with specific skills as required by firms? We have found by analysing the data for the agglomeration of Prague that the specialisation structure the supply of new cohort of workers (i.e. the school leavers) was highly consistent with the structure of expected demand of empoyers (i.e. enterprises). Our analysis working with 28 professional types of secondary schools in Prague reveals that the choice of school and profession depends primarily on the industrial structure of both employment opportunities and unemployment threats. As a secondary observation, the structure of new admissions to schools is related to the level of wages, profits, unemployment rates and R&D expenditures in industries. At the same time we could see that the existing official statistics about educational specialisation are insufficiently structured for serving as an efficient instrument for underpinning the labour market-dependent decision making in both families and schools.
Keywords: I21; C21; 330; education; human capital; supply and demand for working skills; employment in industries; Berufswahl; Schule; Bildung; Humankapital; Qualifikation; Arbeitsangebot; Arbeitsnachfrage; Prag